Organizational Stress and Effecting Factors of Forensic Medicine Specialists and Assistants - Aydın, Berna; Çolak, Başar; Balcı, Yasemin; Kartal, Mehtap (The Bulletin of Legal Medicine, 2010)
Employees experience physical, psychological and social changes by exposure to different factors of stress in the work place. It has been aimed in this study to assess the organizational stress levels of forensic medicine specialists and assistants and the sociodemographic variables that can affect it. The Organizational Stress Survey (VOS-D) has been used to identify and estimate the levels of the organizational stress factors. The version of the survey in the Turkish language has been sent by e-mail or conventional postage to 120 forensic medicine specialists and assistants in 27 provinces, of whom 113 have completed and returned the questionnaire. The data have been analyzed using statistical software packages. Of the volunteers who joined the study, 78 (69%) worked for university forensic medicine departments, 28 (24.8%) for the Council of Forensic Medicine of the Ministry of Justice and 7 (6.2%) for the Hospitals associated with the Ministry of Health. The age range and the mean age of these participants were, respectively, 25-62, 35.9+7.3; of whom 70 (61.9%) were specialists in forensic medicine and 43 (38.1%) were assistant experts; and, 87 (77%) were men and 26 (23%) were women. It could be seen from the percentage distribution and the mean scores of the scale that the participants were adversely affected primarily by job responsibility and secondarily by the work overload, which did not significantly differ with respect to gender. While the responsibility factor mostly affected the specialists, the lack of role definition and the uncertainty of career prospects affected mostly the assistants. In conclusion, measures have to be taken for sharing of responsibility and balanced reduction of the work load in order to lessen the stress experienced by the specialists and the assistants working in forensic medicine. Key words: Forensic medicine, organizational stress